2007
DOI: 10.1159/000113042
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Faecal Occult Blood Test and Lactoferrin Latex Agglutination Test in Screening Hospitalized Patients for Diagnosing Inflammatory and Non-Inflammatory Diarrhoea in Dhaka, Bangladesh

Abstract: Background: Inflammatory diarrhoea (ID) resulting from Shigella, Salmonella, Campylobacter and Entamoeba histoly-tica requires specific diagnosis for therapy. Differentiation between ID and non-inflammatory diarrhoea (NID) is often not clinically possible. A faecal occult blood test (FOBT) correlates with faecal leucocytes. Lactoferrin indicates an inflammatory process as a marker for faecal leucocytes. We evaluated diagnostic values of lactoferrin latex aggluti- nation test (LT) either alone or in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Lactoferrin is an iron binding glycoprotein found in neutrophils and in secretions such as breast milk, and therefore, this marker may be present in feces of children who are breast fed, reducing its utility as an enticing marker for bacterial enteritis in children Ͻ2 years of age (157). This protein is released following neutrophil activation, and the concentrations in stool and other fluids are proportional to the number of neutrophils recruited (158).…”
Section: Evolution Of Testing Methodsmentioning
confidence: 99%
“…Lactoferrin is an iron binding glycoprotein found in neutrophils and in secretions such as breast milk, and therefore, this marker may be present in feces of children who are breast fed, reducing its utility as an enticing marker for bacterial enteritis in children Ͻ2 years of age (157). This protein is released following neutrophil activation, and the concentrations in stool and other fluids are proportional to the number of neutrophils recruited (158).…”
Section: Evolution Of Testing Methodsmentioning
confidence: 99%
“…Where lactoferrin was compared to calprotectin results were similar or poorer than calprotectin. One study in Bangladesh concluded that faecal lactoferrin was not useful in discriminating between inflammatory diarrhoea caused by bacterial infection and non-inflammatory diarrhoea in children 39. The authors considered this may have been due to 45% of children being under 2 years of age and being breast-fed causing false positive results due to maternal lactoferrin and many others being malnourished reducing the inflammatory response leading to false negative results.…”
Section: Lactoferrinmentioning
confidence: 99%
“…The rapid stool assay includes microscopic examination for leukocytes and erythrocytes, but this assay has limited usefulness for discriminating between pathogens in patients with watery diarrhea [4,5]. The fecal occult blood test (FOBT) and lactoferrin latex agglutination tests are rapid, easy, inexpensive, and useful screening tools for inflammatory diarrhea, but require good laboratories with adequately trained technicians, and have low sensitivity and specificity [6]. One laboratory sign of acute gastrointestinal infection is elevation of the level of C-reactive protein (CRP), which has been shown to be a marker of bacterial infection [7,8]; it can also be used to distinguish bacterial from viral infections [9].…”
Section: Introductionmentioning
confidence: 99%